Peran Literasi Keuangan dan Fitur Shopee PayLater dalam Membentuk Pola Konsumsi Mahasiswa Pendidikan Ekonomi Universitas Negeri Semarang Angkatan 2021 - Amalfi Marsha Putri; Suratno Suratno (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study aims to determine the effect of Financial Literacy and Shopee Paylater Features on Consumption Behavior. This study uses a quantitative approach, with a causal design and uses primary data. Data collection was conducted using a questionnaire. The location used in this study is Semarang State University, with the research population consisting of students in the 2021 Economics Education Study Program at Semarang State University. The sampling technique used is purposive sampling, and the Solvin formula is used to determine the sample size. Thus, this study has a total sample of 204. This study uses validity and reliability tests to ensure the validity of the data. This study used descriptive analysis to describe the data and multiple regression analysis to determine the influence of each variable. This study used IBM SPSS Statistics 25 as the analysis tool.